PENGARUH STRATEGI PEMBELAJARAN BANGKITKAN MINAT TERHADAP MOTIVASI BELAJAR EKONOMI PESERTA DIDIK KELAS X DI SMA NEGERI 7 PALEMBANG - Ayu Desi Retnosari; Riswan Jaenudin; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This study aims to determine the differences in the influence of learning strategies generate interest with learning strategy questions prepared against the motivation of learning economics class X students in SMA Negeri 7 Palembang. The population in this study are all the students of class X in SMA Negeri 7 Palembang consisting of eight classes, amounting to 309 students. The sample in this study was taken by using Cluster Random Sampling technique, so selected X.1 class as experiment class and X.3 as control class. Data collection techniques used questionnaires and observations, both observations to see the motivation learners learn and observation to see the implementation of learning strategies. Data collection techniques used questionnaires and observations. Data analysis was done by calculating the percentage of scores obtained based on the visible descriptor and t-test with significance level α = 0.05 or 5% to test the hypothesis. Hypothesis test results obtained t count> 24>ttable 3.7 so it can be concluded that there is a difference in the influence of learning strategies generate interest with learning strategy questions prepared against the motivation to learn economy class X students in SMA Negeri 7 Palembang. From these studies, it is suggested that teachers pay more attention to the learning strategies that will be used and make this interest-motivated learning strategy as an alternative in the learning process, so as to improve the motivation of learners.